Robot-assisted laparoscopic prostatectomy versus open radical retropubic prostatectomy: 24-month outcomes from a randomised controlled study. Issue 8 (August 2018) - Coughlin, Geoffrey D; Yaxley, John W; Chambers, Suzanne K; Occhipinti, Stefano; Samaratunga, Hema; Zajdlewicz, Leah; Teloken, Patrick; Dunglison, Nigel; Williams, Scott; Lavin, Martin F; Gardiner, Robert A
Summary: Background: Previous trials have found similar early outcomes after robot-assisted laparoscopic prostatectomy and open radical retropubic prostatectomy. We report functional and oncological postoperative outcomes up to 24 months after surgery for these two surgical techniques. Methods: In this randomised controlled phase 3 study, men who had newly diagnosed clinically localised prostate cancer and who had chosen surgery as their treatment approach, and were aged between 35 years and 70 years were eligible and recruited from the Royal Brisbane and Women's Hospital (Brisbane, QLD, Australia). Participants were randomly assigned (1:1) to have either robot-assisted laparoscopic prostatectomy or open radical retropubic prostatectomy. Randomisation was computer generated and occurred in blocks of ten. This was an open trial; however, study investigators involved in data analysis were masked to each patient's surgical treatment. Primary outcomes were urinary function (urinary domain of Expanded Prostate Cancer Index Composite [EPIC]) and sexual function (sexual domain of EPIC and International Index of Erectile Function Questionnaire [IIEF]) at 6 months, 12 months, and 24 months and oncological outcome (biochemical recurrence and imaging evidence of progression). The trial was powered to assess health-related and domain-specific quality-of-life outcomes over 24 months. All analyses were done on a per-protocol basis. The trial was registered with the Australian New Zealand Clinical Trials Registry, number ACTRN12611000661976. Findings: Between Aug 23, 2010, and Nov 25, 2014, 326 men were enrolled, of whom 163 were randomly assigned to robot-assisted laparoscopic prostatectomy and 163 to open radical retropubic prostatectomy. 18 withdrew (12 assigned to radical retropubic prostatectomy and six assigned to robot-assisted laparoscopic prostatectomy); thus, 151 in the radical retropubic prostatectomy group and 157 in the robot-assisted laparoscopic prostatectomy group proceeded to surgery. At the 24-month follow-up time point, 150 men remained in the robot-assisted laparoscopic prostatectomy group and 146 remained in the open radical retropubic prostatectomy group. Urinary function scores did not differ significantly between robot-assisted laparoscopic prostatectomy and open radical retropubic prostatectomy at 6 months post-surgery (88·68 [95% CI 86·79–90·58] vs 88·45 [86·54–90·36]; p1<0·0001, p2<0·0001), 12 months post-surgery (90·76 [88·89–92·62] vs 91·53 [90·07–92·98]; p1<0·0001, p2<0·0001), or 24 months post-surgery (91·33 [89·64–93·03] vs 90·86 [89·01–92·70]; p1<0·0001, p2<0·0001). Sexual function scores were not significantly different between robot-assisted laparoscopic prostatectomy and open radical retropubic prostatectomy at 6 months post-surgery (EPIC: 37·40 [33·60–41·19] vs 38·63 [34·76–42·49], p1=0·0001, p2<0·0001; IIEF: 29·75 [26·66–32·84] vs 29·78 [26·41–33·16], p1<0·0001, p2<0·0001), 12 months post-surgery (EPIC: 42·28 [38·05–46·51] vs 42·51 [38·29–46·72], p1<0·0001, p2<0·0001; IIEF: 33·10 [29·59–36·61] vs 33·50 [29·87–37·13], p1=0·0002, p2<0·0001), or 24 months post-surgery (EPIC: 45·70 [41·17–50·23] vs 46·90 [42·20–51·60], p1=0·0003, p2<0·0001; IIEF: 33·95 [30·11–37·78] vs 33·89 [29·82–37·96], p1=0·0003, p2=0·0004). Equivalence testing on the difference between the proportion of biochemical recurrences between the two groups (13 [9%] in the open radical retropubic prostatectomy group vs four [3%] in the robot-assisted laparoscopic prostatectomy group) showed that equality between the two techniques could not be established based on a 90% CI with a prespecified margin of 10%. However, a superiority test showed that the two proportions were significantly different (p=0·0199). Equivalence testing on the proportion of patients who had imaging evidence of progression revealed that the two groups were not significantly different (p=0·2956). Interpretation: Robot-assisted laparoscopic prostatectomy and open radical retropubic prostatectomy yielded similar functional outcomes at 24 months. We advise caution in interpreting the oncological outcomes of our study because of the absence of standardisation in postoperative management between the two trial groups and the use of additional cancer treatments. Clinicians and patients should view the benefits of a robotic approach as being largely related to its minimally invasive nature. Funding: Cancer Council Queensland.